1997
DOI: 10.1099/00222615-46-10-873
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characteristics and lipopolysaccharides of human and animal isolates of Fusobacterium necrophorum

Abstract: As part of a collaborative study, six culture collection isolates and 50 coded isolates of Fusobacterium necrophorum were examined for the types of lipopolysaccharides (LPS) they contained, and to see if this related to their reactions in a range of phenotypic tests and their susceptibility to a panel of six antimicrobial compounds. The biotype B type strain, putative biotype B isolates and human isolates were predominantly coccobacillary, had rough type LPS and some of these isolates (8 of 26) required incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Some describe F. necrophorum subsp. funduliforme as lipase-negative [1,38,44], whereas others describe it as weakly lipase-positive [7,52]. F. necrophorum subsp.…”
Section: Microbiology and Pathogenesismentioning
confidence: 99%
“…Some describe F. necrophorum subsp. funduliforme as lipase-negative [1,38,44], whereas others describe it as weakly lipase-positive [7,52]. F. necrophorum subsp.…”
Section: Microbiology and Pathogenesismentioning
confidence: 99%
“…Previous studies have shown that LPS from human strains resembles that of animal subsp. funduliforme in composition (being rich in amino sugars) (Brown et al, 1997). Studies to determine the biological activity of LPS have revealed that it is less toxic to rabbits (Hofstad & Kristoffersen, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…necrophorum, while the human isolates were distinct and could not be characterized simply as animal "biotype B isolates." Brown et al (70) examined phenotypic characteristics and lipopolysaccharides of human and animal strains and found that human isolates were predominantly coccobacillary, whereas animal isolates were predominantly rod shaped. In addition there were differences in the lipopolysaccharides of the strains from the two sources.…”
Section: Bacteriologymentioning
confidence: 99%